Study ritz method for Poisson equation with Dirichlet and Neumann boundary conditions - Hanafi, Lukman; Mardlijah; Utomo, Daryono Budi (AIP conference proceedings, 2022)
The mathematical formulation of heat conduction problem along the rod in steady state leads to differential equation namely Poisson equation. The Dirichlet and Neumann boundary conditions are known. In this paper, we study Ritz method as construction of approximation solution based on its extreme formulation. This method applied to Poisson equation with Dirichlet and Neumann boundary conditions by choosing finite basis functions to find approximation solution. From the numerical experiment we obtain good approximation solution.